Equity considerations in clinical practice guidelines for traumatic brain injury and homelessness: a systematic reviewResearch in context - Vincy Chan; Maria Jennifer Estrella; Sara Hanafy; Zoe Colclough; Julie Michele Joyce; Jessica Babineau; Angela Colantonio (EClinicalMedicine, 2023)
Summary: Background: Clinical practice guidelines (CPGs) predominantly prioritise treatment and cost-effectiveness, which encourages a universal approach that may not address the circumstances of disadvantaged groups. We aimed to advance equity and quality of care for individuals experiencing homelessness and traumatic brain injury (TBI) by assessing the extent to which homelessness and TBI are integrated in CPGs for TBI and CPGs for homelessness, respectively, and the extent to which equity, including consideration of disadvantaged populations and the PROGRESS-Plus framework, is considered in these CPGs. Methods: For this systematic review, CPGs for TBI or homelessness were identified from electronic databases (MEDLINE, Embase, CINAHL, PsycINFO), targeted websites, Google Search, and reference lists of eligible CPGs on November 16, 2021 and March 16, 2023. The proportion of CPGs that integrated evidence regarding TBI and homelessness was identified and qualitative content analysis was conducted to understand how homelessness is integrated in CPGs for TBI and vice versa. Equity assessment tools were utilised to understand the extent to which equity was considered in these CPGs. This review is registered with PROSPERO (CRD42021287696). Findings: Fifty-eight CPGs for TBI and two CPGs for homelessness met inclusion criteria. Only three CPGs for TBI integrated evidence regarding homelessness by recognizing the prevalence of TBI in individuals experiencing homelessness and identifying housing as a consideration in the assessment and management of TBI. The two CPGs for homelessness acknowledged TBI as prevalent and recognised individuals experiencing TBI and homelessness as a disadvantaged population that should be prioritised in guideline development. Equity was rarely considered in the content and development of CPGs for TBI. Interpretation: Considerations for equity in CPGs for homelessness and TBI are lacking. To ensure that CPGs reflect and address the needs of individuals experiencing homelessness and TBI, we have identified several guideline development priorities. Namely, there is a need to integrate evidence regarding homelessness and TBI in CPGs for TBI and CPGs for homelessness, respectively and engage disadvantaged populations in all stages of guideline development. Further, this review highlights an urgent need to conduct research focused on and with disadvantaged populations. Funding: Canada Research Chairs Program (2019-00019) and the Ontario Ministry of Health and Long-Term Care (Grant #725A).